A framework of governance for the schools of the United Evangelical Churches in the Philippines - Son, Leonides T. (Animo Repository, 2008)
The study primarily aimed to develop a framework of governance for the schools of the United Evangelical Churches in the Philippines. This is to evaluate the existing components, characteristics and functions of the governance of the respective Board of Trustees of the participant schools and how to improve them by coming up with a framework. Case study research method was used to gather data from the individual participant schools through its respective members of the school board. Each school board was treated as an individual case, where a triangulation of data was done through the interviews conducted with members of the school board, review of existing school documents and questionnaire that was sent to members of the school board. Data from the nine case studies were consolidated through pattern-matching that determined the actual governance of the participant schools. Afterwards, the result was cross-analyzed with the contextual literature. The results of the analysis guided the conceptualization of the framework of governance that includes important role of clearly defined ownership which is the core of school board. This will help the board to organize themselves for self- governance which includes vision-mission, structure, obligations, infrastructure, identification, recruitment and selection, orientation and development, and board self-assessment. After organizing themselves, the board can now effectively function as a governing body of the institution that includes policy-making, decision-making, strategic planning, legal responsibilities, financial responsibilities, board-principal/CEO relations, board-constituency relations, and fund-raising. The study contributed to the literature on educational management, particularly in the area of school governance from primary to secondary educational institutions.